2014
DOI: 10.7860/jcdr/2014/8245.4816
|View full text |Cite
|
Sign up to set email alerts
|

“Comparative Efficacy of Different Doses of Fentanyl on Cardiovascular Responses to Laryngoscopy and Tracheal Intubation”

Abstract: IntrOductIOnLaryngoscopy and tracheal intubation can cause tachycardia, hypertension, dysarrhythmias, perioperative myocardial ischaemia, acute heart failure, and cerebrovascular accidents in susceptible individuals [1] .These responses are due to intense sympathetic discharge caused by stimulation of upper respiratory tract, evidenced by rise in catecholamine's. Various drugs and techniques like, topical and IV Lignocaine, deepening level of anaesthesia, adrenergic blockers, vasodilators like, alpha blockers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The onset and action duration of fentanyl is 2 to 3 minutes and 3 hours 39 minutes, respectively. [7,20] While intravenous oxycodone has an onset similar to that of fentanyl, it has a longer action duration (4 hours 52 minutes) than that of fentanyl. [7,20] The peak effect of fentanyl and oxycodone is achieved within 5 minutes and 15 to 30 minutes after intravenous injection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The onset and action duration of fentanyl is 2 to 3 minutes and 3 hours 39 minutes, respectively. [7,20] While intravenous oxycodone has an onset similar to that of fentanyl, it has a longer action duration (4 hours 52 minutes) than that of fentanyl. [7,20] The peak effect of fentanyl and oxycodone is achieved within 5 minutes and 15 to 30 minutes after intravenous injection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5 μg/kg fentanyl was suggested to completely abolish the hemodynamic responses to tracheal intubation in another study. [9] However, there have not been enough trials to determine the optimal dose of IV oxycodone to minimize the changes in HR and BP after intubation.…”
Section: Discussionmentioning
confidence: 99%
“…However, 4 μg/kg fentanyl was needed to achieve stabilization of HR and MAP in patients with hypertension. [3] Hosalli et al [9] found no statistically significant difference in the mean HR between a fentanyl 3 μg/kg group and a 5 μg/kg group in healthy patients without hypertension. There was another study that evaluated hemodynamic response to intubation using alfentanil, esmolol, and their combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] DEX has a relatively high ratio of α 2 /α 1 -activity, the α 2 :α 1 binding selectivity ratio 1620:1; therefore, DEX is a highly specific and selective α 2 -adrenergic receptor agonist. [ 10 11 ] Previous studies that had used intravenous (IV) boluses of DEX showed decrease in BP and cardiac output after small boluses (0.25–1 μg/kg), which were associated with decrease in serum norepinephrine concentration. [ 12 13 ] Review of previous literature showed that DEX has been extensively used for attenuation of pressor response during laryngoscopy and tracheal intubation, but literature on attenuation of pressor response during TT change is not available.…”
Section: Introductionmentioning
confidence: 99%